The student's companion to social policy - Alcock, Peter , 1951-; May, Margaret , 1947-; Wright, Sharon (Wiley-Blackwell, 2012)
The fourth edition of The Student's Companion to Social Policy maintains the text's inimitable and best-selling approach. Written by a wide range of experts in the field, it has been extensively updated and revised to take account of recent developments and debates and changing political and economic configurations